Analisis Kemampuan Literasi Matematis Siswa dalam Menyeleesaikan Soal SPLDV Ditinjau dari Adversity Quotients (AQ) - Ni'mah, Oktaviani Luthfiyyatun; Swastika, Annisa (Jurnal Pendidikan Matematika : Judika Education, 2024)
This study aims to provide a description of students' mathematical literacy skills when working on SPLDV story problems seen from Adversity Quotients. The method applied in this study is a qualitative description. The subjects in this study included 20 students of class VIII A of SMP N 3 Ngawen. There were 3 students representing each type of Adversity Quotients. The instruments applied in this study were in the form of an AQ questionnaire, SPLDV story problems, and also interview guidelines. The results of this study on the climber subject already had good mathematical literacy because they succeeded in working on all indicators of mathematical literacy. The champers subject was already good in mathematical literacy, it was just that the champers subject needed more time than the climbers subject to understand the questions given. The champers subject was more quickly satisfied with his work than the climbers subject. While the quitter subject had a very low level of mathematical literacy because this subject had given up. The conclusion of this study is that climbers subjects have good mathematical literacy, champers subjects are quite good but need more time and are easily satisfied, while quitters subjects have low mathematical literacy because they have given up. Keywords: Adversity Quotients, Mathematical Literacy, SPLDV